SPATIALIZATION OF THE RELATIVE AIR HUMIDITY TO A REGION OF THE SUB-MIDDLE OF SÃO FRANCISCO - LOPES, Iug; LEAL, Brauliro Gonçalves (Brazilian Journal of Biometrics, 2018)
Among the meteorological variables that make up the calculation of the water balance, we have a highlight for the relative humidity, and with measurements of point form can be transformed into continuous fields using spatial interpolation methods. The objective of this work was to evaluate the power of the Inverse Distance Power (IDP) in the spatial daily values of relative humidity in the Petrolina-Juazeiro Development Pole, Brazil, for the seasons: winter, spring, summer, and autumn. The power parameters of the Inverse Distance Power interpolator of the minimum, mean and maximum relative humidity were obtained from the data measured in 14 INMET automatic meteorological stations in operation at the Petrolina-Juazeiro Development Pole. Interpolations were performed for annual, winter, spring, summer and fall seasons. The daily variation of the mean relative error was calculated using the data of minimum, mean and maximum relative humidity. The value of the power of the interpolator obtained for the year time were equal to 2.9; 3.0 and 2.9, respectively. The mean error values were relatively small compared to the instrumental error.